Death anxiety among New Zealanders: the predictive role of gender and marital status - MacLeod, Roderick (Mental health, religion & culture, 2016)
The aim of this cross-sectional study was to investigate attitudes of New Zealanders towards death and dying. We administered an online version of Collett-Lester Fear of Death Scale and Concerns About Dying Instrument subscales to a representative sample of the New Zealand population. In total, 1001 people responded to the survey. Women reported more anxiousness concerning their own death (p = .001) and dying at a young age (p > .001). Women also showed more agreement towards spiritual aspects of dying (p > .001). Single female respondents worry more about dying (p = .02) especially when young (p = .003). Single participants (p > .001) aged 18 and 29 (p > .001) reported higher anxiety for Items relating to the death of others especially concerning never being able to communicate with the person again. Our findings show that marital status and gender strongly predict higher levels of death anxiety among New Zealanders. This is probably due to the cultural identity of those sampled.